Who needs capacity?. (May 2015) - Buchanan, Alec
Abstract: The UK Law Commission's Discussion Paper, Criminal Liability: Insanity and Automatism, recommends introducing the concept of capacity to the insanity defence. The concept of capacity has an established role in those parts of the law that concern the validity of the decisions that people make, for instance in composing a will or entering into a contract. Making mental capacity a criterion for criminal responsibility in a mentally disordered defendant, however, is potentially problematic. First, the term capacity already has several different meanings in the literature on the jurisprudence of mental abnormality. Second, using the concept of capacity in the way that the Law Commission proposes poses difficulties that relate to the provision of testimony by expert witnesses.